Changement technologique et sociabilité : les trois âges des communautés virtuelles africaines - Gado ALZOUMA (Tic & Société)
In this article, we examine the multiple facets of the links created over the past 25 years among digital users as they participate in African virtual communities. The two main questions that guided this research are: What different types of virtual communities have digital practices and appropriation produced in Africa? How do the general structures of these communities and their configurations change over time with the evolution of the federating technical object? To answer these questions, we will pay particular attention to technical changes and to the new forms of sociability made possible by the use of innovative applications, particularly social networks and messaging services such as WhatsApp, as well as to the emergence of an African digital culture that shows itself in the exponential growth of indigenous applications, the creation of African startups, and the colonization of the African imaginary by digital representations in art and leisure activities.